Chitosan Based Periodontal Pocket Inserts - Formulation, In vitro and Preliminary Clinical Evaluation - Balasubramaniam J.; Kumar M.T.; Barat R.; Pandit J.K.; Mittal N. (My University, 2025)
The present paper concerns the in vitro and clinical evaluation of chitosan based periodontal inserts of ciprofloxacin hydrochloride (CPH). The effects of polymer concentration, plasticizer, drug loading and type and concentration of cross-linking agents (formaldehyde and glutaraldehyde) on CPH release were studied. The release of CPH followed a Q vs t1/2 profile. An increase in the plasticizer concentration (propylene glycol and glycerol) and drug loading resulted in a higher rate of CPH release, but the type of plasticizer did not show any significant effect on drug release, whereas retardation was observed with an increase in polymer concentration and cross-linking. Clinical evaluations of the inserts were carried out in patients suffering from periodontitis with an average pocket depth of > 5 mm. Significant improvements were observed in various clinical indices as: Peridontal Index (PI), Bleeding Index (BI), Periodontal Disease Index (PDI), Shick-Ash Modification of Plaque Criteria (SAPC) and Gingival Index (GI) and microbial parameters (% of G (+)and G (-) bacteria and Total Bacterial Count - TBC) at the device inserted site, thus affirming the therapeutic value of the inserts in the treatment of periodontal pocket formation.